Financial Sector Assessment : Poland - World Bank (Washington, DC, 2013)
The principal objectives of this financial sector assessment were to assist the authorities in identifying potential vulnerabilities in the Polish financial system that could have macroeconomic consequences, to suggest measures to reduce these risks, and to outline development needs in the system and strategies to address these concerns. The purpose of this note is to provide a summary of the main findings of the mission, together with the policy priorities identified. The issues facing the Polish financial sector are mostly of development rather than stability nature. Poland has made significant reforms in its financial sector over the last decade, with an acceleration of the restructuring of its banking system in the last three years. Poland has completed the larger part of the transition-related reform agenda in the financial sector. While the overall stability of the financial sector does not appear to be a concern at the moment, enhanced oversight of risk management systems of financial institutions and improvements in crisis prevention and management procedures are necessary.